Implementación de un sistema de adquisición de datos para la máquina de ensayos a la tracción construida en el AEIRNNR. - Cuenca, Fanny (2007)
Nowadays the technological advances are more and more important, is therefore that the National University of Loja this preparing itself for this new scene. As it stops of this technological scientific development the Area of Energy Natural Industry and non-Renewable Resources, it raises east project of Data acquisition for the Machine of Tests to the Traction that is in the mechanical factory, to fortify the knowledge of the students and to provide the professors with new tools to verify his concepts with new methodologies directed in applied sciences. The present state of the machine of tests to traction presents/displays a low trustworthiness of results, and has a limited man-machine interface, in addition the compilation to the data of manual way. The present work consists of the acquisition, analysis and presentation of data by computer of the Machine of Tests to the Traction. It was begun first by the identification of the involved variables, the selection will be made of the sensors implement for each identified variable as they are the force and the deformation (cell of load and satin gages), later will be made the design and construction of the complementary elements for the implementation of the sensors in this case will be constructed an electronic circuit to be able to adapt the signal to the ranks of operation of the modules of data acquisition (Compact Field Point), soon took place the calibration of the cell as well as of the device to measure the deformation, finally with the aid of the computational program LabVIEW which will provide data in real time and this designed specially for the direct communication with the devices of measurement of field (sensorial); the data could be manipulated, be analyzed and presented/displayed in the screen in graphical form, also this program offered the possibility of generating reports of which they could be printed and be stored.